Análisis biomecánico del efecto de las zapatillas de clavos en el rendimiento del esprint en hombres velocistas - Corbi-Santamaria, P.; Jiménez-Velayos, A.; Corbi-Santamaria, M.; Garcia-Lopez, J. (Revista Internacional de Ciencias del Deporte, 2018)
The purpose of the present study was to quantify the effect of the use of spikes on sprint performance in male athletes, separating between both cleats and mass effects; additionally, the influence of the footwear on biomechanical parameters of running was analyzed. Nine male regional-national sprint athletes (i.e., 100, 200 and 400 m distances) participated in this study, they performed three 40 m sprints in a randomized order (i.e., spikes, running shoes and mass-added spikes). Performance improved 2,6% with spikes with respect to running shoes, where 1,7% was due to the cleats and 0,9% was due to the mass. When analyzing the biomechanical variables, it was observed that the speed increased because both step rate and step length also increased. Step length increased and the contact time decreased due to a combined effect of the cleats and the mass. In conclusion, the sprint performance improved when using spikes with respect to running shoes, two third of the improvement was due to the cleats, and the rest to the shoe`s mass.